1986
DOI: 10.1111/j.1365-2672.1986.tb01092.x
|View full text |Cite
|
Sign up to set email alerts
|

Scanning electron microscopy preparation methods: their influence on the morphology and fibril formation in Pseudomonas fragi (ATCC 4973)

Abstract: The use of cryo‐scanning electron microscopy (cryo‐SEM) in the study of the morphology of Pseudomonas fragi (ATCC 4973) revealed gross differences when compared to material prepared using conventional chemical methods. Changes associated with each step of the chemical preparatory procedure were monitored by cryo‐SEM. It appeared that fibril formation was associated with the ethanol dehydration stage of the chemical preparation method and was not an attachment feature of these cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1987
1987
1996
1996

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Tyler & Marshall (1967) suggested that soil bacteria produce some holdfast material to give more permanent binding to the surface. Fraser & Gilmour (1986) reported that visible fibrillar material is an artefact of sample preparation, but accumulating electron microscopy data, obtained by use of different techniques in various bacteria-surface interactions, are not in accordance with this opinion (Foster, 1986).…”
Section: Discussionmentioning
confidence: 97%
“…Tyler & Marshall (1967) suggested that soil bacteria produce some holdfast material to give more permanent binding to the surface. Fraser & Gilmour (1986) reported that visible fibrillar material is an artefact of sample preparation, but accumulating electron microscopy data, obtained by use of different techniques in various bacteria-surface interactions, are not in accordance with this opinion (Foster, 1986).…”
Section: Discussionmentioning
confidence: 97%
“…Pseudomonas fragi (ATCC 4973), Pseudomonas fluorescens, and Acinetobacter spp. have been reported to produce biofilm (89)(90)(91)(92)(93)(94)(95)(96)(97)(98)(99)(100). Salmonella typhimurium and Yersinia enterocolitica were reported as biofilm producers at the IAMFES conference (International Association of Milk, Food, and Environmental Sanitarians) in 1990.…”
Section: Food Industrymentioning
confidence: 98%
“…In all investigated specimens, the bacterial cover was detached from the host surface and the bacteria appeared to adhere more firmly to one another. The mucous matrix in which the bacteria were embedded probably shrank during the preparation process [21], but is still visible as small fibers interconnecting the individual cells (Fig. 1B).…”
Section: Types and Morphology Of Bacterial Coatsmentioning
confidence: 99%